The Impact of Leverage on Investment for Firms Listed in the Indonesian Stock Exchange - Sri Hermuningsih; Pristin Prima Sari; Anisya Dewi Rahmawati (Forum Inovasi Bisnis dan Manajemen, 2020)
Food and beverage firms listed in Indonesia Stock Exchange (IDX) that have opportunities to grow and develop and predicted to be improved. Food and beverage firms needed by mankind because of basic ingredient. Food and beverage firms engaged in manufacturing products and ordering to obtain large profits. Achieving these objectives, management need high level of effectiveness that is required. Firm management faced by various kinds of corporate financial decisions, one of which is investment decisions. Investment decision must consider factors such as the leverage ratio. The main adjective is to examine and obtain evidence about the impact of leverage on investment decisions in a food and beverage firm listed on the Indonesian Stock Exchange. The study used a quantitative approach with purposive sampling technique. The population used in this study were food and beverage firms from 2015 to 2019. The TKT achievement was TKT 6. The results have finding that leverage with the DAR proxy have a significant positive impact on investment. The greater the leverage, the greater the firm's investment. Research have beneficial for firm shareholders who consider their investment, and also for firm management for developing corporate leverage and investment.